General Social Survey, 1974 - Davis, James A. ([Verlag nicht ermittelbar], 1984)
As in 1972 and 1973, the 1974 interview includes items selected by the NORC staff and an advisory panel of sociologists as "mainstream" interests of academic sociology. In addition to standard personal data items, the 1974 survey covers such areas of interest as the family, socio-economic status, social mobility, and morale. About two-thirds of the questionnaire probed for attitudes and opinions concerning qualities of a job, satisfaction with life, roles of women, birth control and abortion, sex relations, race relations, social control issues, and civil liberties. The data were collected by the National Opinion Research Center as the third in a five-year series of general social surveys. The survey was administered in March 1974 to a national cross-section sample of adults 18 years of age or older. The data was obtained from the Roper Center for Public Opinion Research.